Development of a Teledermatology Service in Rural Washington State Using the Doctor of Nursing Practice Skill Set and Implementation Science. - Hastie Norris, Samantha; Matthews, Sarah W.; Hogan, Molly T. (Journal of the Dermatology Nurses' Association)
Teledermatology increases access to dermatologic care in rural communities and is an effective strategy to decrease unnecessary dermatology referrals. At Confluence Health, the largest rural healthcare organization in Washington State, the average dermatology appointment wait time is approximately 7 months. This delay is more than 6 times the national average wait time of 33.9 days, making the need to increase access to care significant. To address this gap in care, a consultation service using store-and-forward teledermatology was designed, guided by the Knowledge-to-Action framework. This framework is an effective tool used in implementation science to guide the translation of evidence-based knowledge into practice. Store-and-forward telehealth allows for asynchronous electronic transmission of digital images to a specialist who later formulates a diagnostic impression and management plan. Since the outbreak of the COVID-19 pandemic, Confluence Health has swiftly adopted real-time video visits and plans to integrate this store-and-forward teledermatology consultation service by December 2020. This article examines a systems-level quality improvement initiative, facilitated by a Doctor of Nursing Practice-prepared nurse practitioner, with the aim of improving access to care and health outcomes.